Analysis the context of Uncertainty (Nature and management) under two school of strategic thinking (theoretical perspective - السعدي يعرب عدنان (Journal of Economics and Administrative Sciences, 2017)
Purpose: studying and analyzing the nature of uncertainty as part of strategy formulation, through analyzing the uncertainty faced by managers in the modern business environment characterized by high complexity and dynamism, though developing of an idea about the uncertainty cases and how enable the mind to understand these cases. Methodology: It was the use of inductive and analytical approach, in order to study the accumulation of knowledge towards development areas that could contribute to strengthening the strategy formulation. Findings: Mentoring the future will not make the success for business organization but thought business organization ability to developing share mental model for the future will make the future successful. through multiple mental models we can enhance the learning process from the future and that contribute to developing memory of the future that help managers to manage the uncertainty. Originality and value: development approach to strategy formulation as organic process through which to understand the uncertainty, by focusing on the expansion the ideas of cognitive and learning school through orientation towards learning from the future and future memory. Mintzberg consider both cognitive and learning school as Natural by contras with planning school tend to be rational, and as oriented to External word considered both cognitive and learning school tend to be able to deal with Unpredictable and confusing by compare with planning school tend to by controllable and comprehensible, that result lead to expanding in the ideas of both cognitive and learning school